Pengaruh Kepercayaan Diri dan Kemandirian Belajar Terhadap Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Fisika (Survei pada SMA Swasta di Kota Depok) - Fitriani, Nurhikmah; Musliman, Acep; Rahmatullah (ALFARISI: Jurnal Pendidikan MIPA, 2026)
This study aims to determine the influence of self-confidence and learning independence on students’ critical thinking skills in physics subjects for SMS students in Depok City. The research method used is a quantitative approach with a survey research type. Theresearch sample amounted to 88 grade X students from SMA Putra Bangsa, SMA Yapemri, and SMA Yaspen Tugu Ibu, which was determined using the Proportional Random Sampling technique. Data on self-confidence and learning independence were collected through questionnaires, while data on critical thinking skills were obtained through essay tests. The results of this study indicate that there is a positive and significant influence between self-confidence and learning independence on students’ critical thinking skills in physics subjects (Sig = 0.000 <0.05) with F- values of 46.525; 5.252; and 5.964, respectively.